1994
DOI: 10.1055/s-2007-1001668
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Hyperinsulinism as Possible Predisposing Factor for Diabetes Mellitus, Obesity and Enhanced Cardiovascular Risk in Later Life

Abstract: The importance of the intrauterine and neonatal metabolic environment as possible teratogenic determinants of predispositions to diabetes, obesity and cardiovascular diseases is discussed. Epidemiological, clinical and experimental results suggest that gestational diabetes or even slightly impaired glucose tolerance during pregnancy are important risk factors for the development of an increased Type II- and even Type I diabetes susceptibility in the offspring. In addition, early prenatal undernutrition might a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
180
0
19

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 256 publications
(210 citation statements)
references
References 33 publications
7
180
0
19
Order By: Relevance
“…In vitro and other evidence shows that actively insulin-secreting beta cells are more prone to destruction via various mechanisms such as susceptibility to interleukin 1-beta and increased levels of islet antigens [52]. Further experimental animal data have been reviewed and potential mechanisms previously discussed [53]. A number of studies have found postnatal body size or growth to be associated with risk of type 1 diabetes [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and other evidence shows that actively insulin-secreting beta cells are more prone to destruction via various mechanisms such as susceptibility to interleukin 1-beta and increased levels of islet antigens [52]. Further experimental animal data have been reviewed and potential mechanisms previously discussed [53]. A number of studies have found postnatal body size or growth to be associated with risk of type 1 diabetes [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that evidence from the literature has confirmed that rapid neonatal weight gain is the "missing" pathophysiological link between low birthweight and later increased risk of adipogenic and metabolic conditions, as we proposed ten years ago [4]. Clearly, there is a supposition that high and rapid neonatal weight gain is caused by neonatal overnutrition.…”
Section: To the Editormentioning
confidence: 87%
“…In contrast, epidemiological and experimental data exist that suggest that high birthweight as well as rapid neonatal weight gain are independent risk factors for overweight and obesity in later life [3,4,5]. It is worth noting that evidence from the literature has confirmed that rapid neonatal weight gain is the "missing" pathophysiological link between low birthweight and later increased risk of adipogenic and metabolic conditions, as we proposed ten years ago [4].…”
Section: To the Editormentioning
confidence: 91%
See 2 more Smart Citations